БНМАУ Тагна Туватай дипломат харилцаа тогтоосон нь, түүний түүхэн учир холбогдол - Д, Уламбаяр (Journal of International Studies, 2008)
English title: The establishment of diplomatic relations between Peoples Republic of Mongolia and Tuva, its historic importance